Students' Perceptions of the Role of Electronic Media in Enhancing English Language Learning - Hasby, Nazar; Perdana, Indra; Karani, Elanneri; Nurhasanah, Nurhasanah; Kodriyah, Lailatul; Islamiah, Neneng (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2025)
This research aimed to explore the role of electronic media in enhancing English language learning among high school students in Banjarmasin, Indonesia. The research focused on students’ perceptions and their experiences with digital platforms, apps, and social media. The rapid advancement of technology has made electronic media essential tools in Education, offering students flexible, engaging, and interactive learning opportunities. Despite these benefits, challenges such as limited internet access, insufficient digital skills, and lack of direct teacher interaction were also noted. The findings revealed that students found electronic media motivating and enjoyable, particularly in developing listening and speaking skills. They appreciated the easy access to learning materials and the flexibility to learn anytime and anywhere. However, the lack of in-depth teacher explanations and the dependency on a stable internet connection remained significant barriers. The research suggested that while electronic media could significantly enhance language learning, their full potential could only be realized by addressing technological challenges and promoting digital literacy.